Atenolol and metoprolol once daily in hypertension. Issue 6328 (22nd May 1982) - Scott, A K; Rigby, J W; Webster, J; Hawksworth, G M; Petrie, J C; Lovell, H G
Abstract : The effect of once-daily dosage of the two most widely prescribed cardioselective beta-adrenoceptor antagonists used to treat hypertension–namely, atenolol and metoprolol–was studied in nine carefully selected hypertensive outpatients. Each patient received atenolol 50 mg/day, atenolol 100 mg/day, metoprolol 100 mg/day, and metoprolol 200 mg/day in a sustained-release formulation (as Lopresor SR) according to a randomised sequence. After three weeks' treatment with each drug given once daily comparisons of the treatments 24 hours after dosing showed no important differences between 50 and 100 mg atenolol/day. Metoprolol, as both the standard and the slow-release formulations, had some limitations in controlling systolic blood pressure and heart rate. These results suggest that the recommendations for the treatment of hypertension with these cardioselective beta-adrenoceptor antagonists should be reconsidered since doses smaller than those recommended are almost as effective and much cheaper.